Simplified Thermal Evolution of Proto-hybrid Stars - Mariani, Mauro (2017)
We study the possibility of a hadron-quark phase transition in the interior of neutron stars, taking into account different schematic evolutionary stages at finite temperature. Furthermore, we analyze the astrophysical properties of hot and cold hybrid stars, considering the constraint on maximum mass given by the pulsars J1614-2230 and J1614-2230. We obtain cold hybrid stars with maximum masses ≥ 2 M⊙ . Our study also suggest that during the proto-hybrid star evolution a late phase transition between hadronic matter and quark matter could occur, in contrast with previous studies of proto-neutron stars.